Analisis Keuntungan dan Break Even Point ( BEP) Studi Kasus pada Industri Keripik Pisang Tunas Jaya di Manokwari - Kurniawan, Aceng (Fakultas Teknologi Pertanian, Universitas Papua, Manokwari, 2024)
Abstract Small and medium industries (SMEs) play an important role in the Indonesian economy, especially in creating jobs and driving regional economic growth. One of the growing sectors is the snack food industry, including banana chips. This study aims to analyze the level of profit and Break Even Point (BEP) in the Tunas Jaya Banana Chips Industry in Manokwari Regency. A quantitative descriptive approach was used through primary and secondary data collection. The results showed that the total monthly income of this industry reached IDR 16,000,000, with a total cost of IDR 10,380,000. From this calculation, a profit of IDR 5,620,000 per month was obtained. The BEP analysis showed that the break-even point was achieved at the sale of 397 packs with a minimum income of IDR 7,940,000. With an actual production of 800 packs per month, the industry has exceeded BEP and obtained stable profits. This study provides strategic recommendations for business actors in managing finances and improving operational efficiency, including managing fixed and variable costs, to encourage sustainable business growth. Keywords: Chips industry, profit, BEP